Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
63 : [ 39 - 2(2x+1)2] +43 = 67
63 : [ 39 - 2(2x+1)2] +64 = 67
63: [ 39 - 2(2x+1)2] = 67 - 64
63: [ 39 - 2(2x+1)2] = 3
39 - 2(2x+1)2 = 63 : 3
39 - 2(2x+1)2 = 21
2(2x+1)2 = 39 - 21
2(2x+1)2 = 18
(2x+1)2 = 18 : 2
(2x+1)2 = 9
(2x+1)2 = 32
2x+1 = 3
2x = 3 - 1
2x = 2
x = 2 : 2
x = 1
2. A = 3 + 32 + 33 +...+ 3100
=> 3A = 32 + 33 +...+ 3101
=> 3A - A = 3101 -3
=>2A = 3101 - 3
=>2A + 3 =3101 - 3 + 3=3101
Vậy 2A+3 là 1 lũy thừa của 3
1.
a) 2711 và 818
2711 = (33)11 = 333
818 = (34)8 = 332
\(\Rightarrow\) 2711 > 818
=24-67+25=49-67=-18
24 - [67 - (8-3)2]
= 24 - [67 - 52 ]
= 24 - [67 - 25 ]
= 24 - 42
= -18